Dispute Settlement Patterns on The Village Chief Election In Indonesia (Lumajang Regency) - Fauziyah Fauziyah; Sri Praptianingsih (Universitas Muhammadiyah Sidoarjo, 2016)
In the year of 2013, Lumajang Regency carries out 159 village chief election (Pilkades). There are 4 disputes of Pilkades, and all about voice counting result of Pilkades. Local Regulation No. 24 year 2006 and Local Regulation No. 6 year 2012 do not state any matter of dispute in village headman election and mechanism of solution, but Local Government Regulation determines Watchdog Committee in the level of sub-district and Team of Village Governance Issues Completion in the level of District. Watchdog committee conducts supervision by preventive and repressive act. Supervision is done through preventive act in the form of communications and socialization to the village officer, Village Consultative Council (BPD), and Pilkades Committee about the importance of honest, fair and democratic Pilkades. Meanwhile, supervision is conducted through repressive act by facilitating the parties if dispute happened. As the result, committee executes the monitoring well, proven from 159 Pilkades, there was only 4 disputes, three among others can be resolved in non litigation process. Existence of Watchdog Committee is supported by the availability of budget coming from help of region budget (APBD) that is packed into village budget (APBDes), Rp.2.000.000 for every Pilkades.